Strategic Management for Sustainable Ecotourism in Darabad Region in Tehran, Iran - Nouri, J.; Arjm, R.; Moshiri, S.P. (Asian Journal of Chemistry, 2012)
The purpose of this study was to formulate a proper strategy for ecotourism creation in Darabad region, located in the northeast of Tehran, Iran adjacent to Alborz Mountains. This region is one of the tourism and recreational regions, where is considerably potential to attract many visitors and tourists. To achieve this purpose, firstly the status of ecotourism management was evaluated using strengths, weaknesses, opportunities and threats (SWOT) method. In this regards, external and internal factors were measured and gained 2.42 and 2.88 scores, respectively. This indicated the amount of threats exceeding the opportunities and strengths are more than the weaknesses. Secondly, 21 strategies were formulated. For scoring the strategies, quantitative strategic planning matrix was applied and the obtained results were reasonably used for strategic position and action evaluation matrix. The study showed that the present situation of destination, in terms of ecotourism management, is in "competitive" classification. The findings of this study present the need for developing proper promotional plans, in order to introduce regional attractions; developing welfare and safe recreational facilities such as accommodations for enhancing the eco-tourist attractions; identifying and introducing the carrying capacities of tourists and visitors in the region and establishing subtle monitoring plans in order to identify the environmental destructions due to visitors' presence and tourists through the region.